2012
DOI: 10.4161/nucl.21676
|View full text |Cite
|
Sign up to set email alerts
|

A truncated lamin A in the Lmna−/−mouse line

Abstract: During recent years a number of severe clinical syndromes, collectively termed laminopathies, turned out to be caused by various, distinct mutations in the human LMNA gene. Arising from this, remarkable progress has been made to unravel the molecular pathophysiology underlying these disorders. A great benefit in this context was the generation of an A-type lamin deficient mouse line (Lmna−/−) by Sullivan and others,1 which has become one of the most frequently used models in the field and provided profound ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(54 citation statements)
references
References 90 publications
4
50
0
Order By: Relevance
“…1D). In line with an earlier report (26), however, we did find that the Lmna knockout allele yielded trace amounts of an internally truncated form of lamin A (detected with a monoclonal antibody against the amino-terminal region of lamin A/C [22]) (see Fig. S1 in the supplemental material).…”
Section: Lmnb2supporting
confidence: 76%
See 1 more Smart Citation
“…1D). In line with an earlier report (26), however, we did find that the Lmna knockout allele yielded trace amounts of an internally truncated form of lamin A (detected with a monoclonal antibody against the amino-terminal region of lamin A/C [22]) (see Fig. S1 in the supplemental material).…”
Section: Lmnb2supporting
confidence: 76%
“…After breeding mice for this study, Jahn et al (26) reported that this particular Lmna knockout allele produces an internally truncated lamin A, but there was little evidence that this protein is functional-or that it has toxic gain-of-function properties. In our studies, we detected the truncated lamin A in keratinocytes on Western blots, but the level of the protein was very low.…”
Section: Discussionmentioning
confidence: 99%
“…The origin of this signal is unclear but could correspond to the residual A-type lamin protein recently reported in that mouse model. 36 Taken together, and in agreement with the developmental regulation of lamins in other tissues, 37,38 these experiments indicate that B-type lamins are ubiquitously expressed in all RPCs and post-mitotic retinal cells whereas A-type lamins expression appears to be triggered upon exit from the cell cycle in a subset of retinal cell types.…”
Section: Expression Pattern Of Lamins In the Developing Retinasupporting
confidence: 72%
“…Embryonic fibroblasts exhibited striking abnormalities in nuclear shape. Subsequent studies revealed that the knockout mice expressed trace amounts of an internally truncated prelamin A (36). However, that product appeared to be relatively unimportant because the phenotypes of a newer line of Lmna Ϫ/Ϫ mice were similar (37).…”
Section: Proteins Of the Nuclear Laminamentioning
confidence: 99%